2014
DOI: 10.1155/2014/173401
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Endothelial-Derived Activated Microparticle: A Useful Biomarker for Predicting One-Year Mortality in Patients with Advanced Non-Small Cell Lung Cancer

Abstract: Background. This study tested the hypothesis that circulating microparticles (MPs) are useful biomarkers for predicting one-year mortality in patients with end-stage non-small cell lung cancer (ES-NSCLC). Methods and Results. One hundred seven patients were prospectively enrolled into the study between April 2011 and February 2012, and each patient received regular follow-up after enrollment. Levels of four MPs in circulation, (1) platelet-derived activated MPs (PDAc-MPs), (2) platelet-derived apoptotic MPs (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 47 publications
(70 reference statements)
3
41
0
Order By: Relevance
“…Discordant results emerged from another study conducted in 107 end-stage nonsmall cell lung cancer patients, divided into 1-year survivors and nonsurvivors, measuring PMPs and EMPs [60]. While there was no difference in PMPs and "apoptotic" EMPs (defined as CD31 + CD42b − annexinV + microparticles) between the two groups, "activated" EMP levels (defined as CD31 + CD42b − annexinV − microparticles) were significantly higher in nonsurvivors [60]. After a multivariate regression analysis, these higher levels were an independent predictor of 1-year mortality.…”
Section: Lung Cancermentioning
confidence: 91%
See 1 more Smart Citation
“…Discordant results emerged from another study conducted in 107 end-stage nonsmall cell lung cancer patients, divided into 1-year survivors and nonsurvivors, measuring PMPs and EMPs [60]. While there was no difference in PMPs and "apoptotic" EMPs (defined as CD31 + CD42b − annexinV + microparticles) between the two groups, "activated" EMP levels (defined as CD31 + CD42b − annexinV − microparticles) were significantly higher in nonsurvivors [60]. After a multivariate regression analysis, these higher levels were an independent predictor of 1-year mortality.…”
Section: Lung Cancermentioning
confidence: 91%
“…FLEITAS et al [59] found higher levels of total circulating microparticles in 60 patients with nonsmall cell lung cancer compared with 60 controls, but the most relevant finding was that, in cancer patients, higher baseline levels of microparticles were associated with a better progression-free and overall survival. Discordant results emerged from another study conducted in 107 end-stage nonsmall cell lung cancer patients, divided into 1-year survivors and nonsurvivors, measuring PMPs and EMPs [60]. While there was no difference in PMPs and "apoptotic" EMPs (defined as CD31 + CD42b − annexinV + microparticles) between the two groups, "activated" EMP levels (defined as CD31 + CD42b − annexinV − microparticles) were significantly higher in nonsurvivors [60].…”
Section: Lung Cancermentioning
confidence: 94%
“…SEM also has significant drawbacks related to preparation of sample(s), with purified EVs inconsistently being immobilized onto the substrate (silica wafers or mica) for SEM imaging. 60 Atomic force microscopy is another valuable tool that enables the determination of ultrastructure for all entities (EVs, plasma proteins) at an atomic resolution. 48 Most recently, this technique was used to understand the ultrastructure of purified platelet MPs 48 and is the only instrument that offers information regarding protein contamination in purified EV fraction owing to its atomic level of resolution.…”
Section: Limitation Of Previous Methods Of Ev Characterization and Qumentioning
confidence: 99%
“…The term 'platelet dust' was later replaced with 'microparticles' 57 and 'exosomes', 58 in which platelet MPs are membrane-derived and exosomes being the exocytosed storage granules (alphagranules, dense granules) of platelets. EVs, either MPs or exosomes, are secreted by platelets, 59 endothelial cells 60 and leukocytes, 61 and these types of cell fragments are relatively abundant in different bodily fluids. 2 Through quantification of all circulating MPs in vivo, it is now understood that platelet EVs are the most abundant types of EVs, when compared with MPs from other circulating cells.…”
Section: Platelet Mpsmentioning
confidence: 99%
“…Although elevated level of apoptotic EMPs have demonstrated high predictive value for CHF development and clinical outcomes [21][22][23][24], the role of activated EMPs is still not clear. Probably CHF development is the result of both disease-specific and traditional cardiovascular risk factors contributed an imbalance between apoptotic-derived EMPs and activated EMPs forming impaired phenotype.…”
mentioning
confidence: 99%